2017
DOI: 10.4236/ojemd.2017.71005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Physical Exercise on Obesity

Abstract: Obesity is a disease of epidemic proportions, associated with chronic inflammation in response to increased secretion of inflammatory cytokines originating in adipose tissue. Exercise has been shown to be effective in combating these changes. The aim of this study was to review the anti-inflammatory effect of physical exercise in the pathogenesis of obesity. We conducted a search of the terms "exercise", "obesity" and "inflammation" on Medline and PubMed databases, restricting results to clinical trials publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, discovering new alternatives to prevent the accumulation of visceral fat and mobilization of adipokines is of the utmost importance when modulating energy homeostasis and insulin sensitivity. Studies have shown that aerobic or anaerobic exercises may be effective (Zanuso et al, 2010) in the treatment of obesity (Figueiredo et al, 2017) and diabetes (Plomgaard and Weigert, 2017). Exercise promotes increases in the systemic levels of anti-inflammatory cytokines such as Interleukin-4 (IL-4), Interleukin (IL-10) (Balducci et al, 2010) and adiponectin (Miyazaki et al, 2010), and stimulates the C-X-C motif chemokine ligand 8 (CXCL8), a cytokine that acts as an angiogenic factor in human microvascular endothelial cells (Ostrowski et al, 2001), and is associated with insulin resistance and obesity (Bruun et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, discovering new alternatives to prevent the accumulation of visceral fat and mobilization of adipokines is of the utmost importance when modulating energy homeostasis and insulin sensitivity. Studies have shown that aerobic or anaerobic exercises may be effective (Zanuso et al, 2010) in the treatment of obesity (Figueiredo et al, 2017) and diabetes (Plomgaard and Weigert, 2017). Exercise promotes increases in the systemic levels of anti-inflammatory cytokines such as Interleukin-4 (IL-4), Interleukin (IL-10) (Balducci et al, 2010) and adiponectin (Miyazaki et al, 2010), and stimulates the C-X-C motif chemokine ligand 8 (CXCL8), a cytokine that acts as an angiogenic factor in human microvascular endothelial cells (Ostrowski et al, 2001), and is associated with insulin resistance and obesity (Bruun et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increasing physical fitness, a recent metareview suggested that aerobic and resistance exercises with moderate intensity are able to reduce the inflammatory biomarkers CRP, IL-6, and tumor necrosis factor-α in blood 38 . Low to moderate intensive aerobic exercise is also effective in reducing inflammation and improves metabolic markers in individuals with obesity and metabolic syndrome 39 . A comprehensive exercise guideline for cancer survivors to improve physical fitness and health-related quality-of-life has been published recently 40 and may be adapted to improve their current status.…”
Section: Discussionmentioning
confidence: 99%
“…Even with this slight inflammatory activation caused by the diet, it is noteworthy that HIIT in obese animals reduced the levels of IL-6, IL-10, and adiponectin. It is known that the stress promoted by physical exercise is linked to an increase in catecholamine discharge and that the catecholamine receptors present in macrophages have great importance in modulating the inflammatory response (Figueiredo et al, 2017). In the condition of obesity, a high-fat diet could lead to an increase in catecholamines, which, in turn, via cAMP response elementbinding protein, would suppress the expression of adiponectin (Liu and Liu, 2009).…”
Section: Discussionmentioning
confidence: 99%